The Impact of Childhood Maltreatment on Aggression in Elementary School Students: The Mediating Role of Callous-Unemotional Traits and Self-Control - Fathi Hashroudi, Roujina; Pali, Samira (Iranian Journal of Neurodevelopmental Disorders, 2026)
Purpose: The present study aimed to investigate the effect of childhood maltreatment on aggression among elementary school students with the mediating roles of callous-unemotional traits and self-control.Methods and Materials: The present study was applied in terms of purpose and descriptive-survey in terms of methodology. The statistical population consisted of male and female lower secondary school students in Lahijan during 2025, from whom 359 participants were selected using the Krejcie and Morgan table and stratified random sampling. Data were collected using the Aggression Questionnaire (AQ) developed by Arnold H. Buss and Mark Perry (1992), the Childhood Trauma Questionnaire developed by David P. Bernstein et al. (2003), the Callous-Unemotional Traits Scale developed by Paul J. Frick et al. (2006), and the Self-Control Scale developed by June P. Tangney et al. (2004). Data analysis was conducted using descriptive statistics, the Kolmogorov–Smirnov test, and Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) approach using SmartPLS software at a 95% confidence level.Findings: The findings demonstrated that childhood maltreatment had a significant positive effect on aggression (β = 0.485, t = 8.390) and callous-unemotional traits (β = 0.587, t = 15.096), while it had a significant negative effect on self-control (β = -0.630, t = 18.692). In addition, callous-unemotional traits positively predicted aggression (β = 0.267, t = 4.970), whereas self-control negatively predicted aggression (β = -0.214, t = 4.262). The bootstrapping results further indicated that callous-unemotional traits and self-control significantly mediated the relationship between childhood maltreatment and aggression. The structural model also demonstrated satisfactory fit and predictive power (GOF = 0.392).Conclusion: The findings suggest that childhood maltreatment contributes to aggressive behavior among students both directly and indirectly through emotional and self-regulatory mechanisms. Specifically, exposure to maltreatment increases callous-unemotional traits and reduces self-control, which subsequently intensify aggressive tendencies.